Free Flap Donor-Site Complications and Management - Archibald, Hunter; Stanek, Joel; Hamlar, David (Seminars in Plastic Surgery, 2022)
Free flap harvest will occasionally result in donor-site complications and morbidity. Most of these complications are managed simply without producing lingering effects on activities of daily living. However, some patients will sustain limb weakness, gait issues, chronic pain, and nonhealing wounds. Frank preoperative discussion between surgeon and patient is essential to maximize postoperative outcome and manage expectations. Fastidious surgical technique will help minimize the risks of hematoma, seroma, and infection, while newer techniques can help prevent some issues with wound healing, limb weakness, and sensory changes. In this article, we describe the rates of common and rare complications at free flap donor sites, as well as techniques to prevent and manage them.
Keywords: free tissue flaps; reconstructive surgical procedures; morbidity